Brain system segregation and pain catastrophizing in chronic pain progression - Delgado-Gallén, Selma; Soler, MD; Cabello-Toscano, María; Abellaneda-Pérez, Kilian; Solana-Sánchez, Javier; España-Irla, Goretti; Roca-Ventura, Alba; Bartrés-Faz, David; Tormos, Josep M.; Pascual-Leone, Alvaro; Cattaneo, Gabriele (Frontiers in Neuroscience, 2023)
Pain processing involves emotional and cognitive factors that can modify pain perception. Increasing evidence suggests that pain catastrophizing (PC) is implicated in the maladaptive plastic changes related to the development and maintenance of chronic pain (CP). These changes have been studied with functional magnetic resonance imaging (fMRI) and have shown an association between CP and two main networks: default mode network (DMN) and dorsoattentional network (DAN). These alterations are thought to be related to different phenomena, like pain-related self-thoughts, the constant attentional resources destined for internal stimuli, or the search for pain relief. Brain system segregation degree (SyS), an fMRI framework used to quantify the extent to which functional networks are segregated from each other, is associated with cognitive abilities in healthy individuals or with neurological diseases. We hypothesized that individuals suffering from CP would show worst health-related status and differences in fMRI compared to healthy individuals and that, within CP individuals, longitudinal changes in pain experience (pain intensity and affective interference), could be predicted by SyS and PC subdomains (rumination, magnification, and helplessness). We first assessed the sociodemographic and health-related data from online questionnaires of 347 individuals (mean age=53,84, 55,2% women). To assess the longitudinal progression of CP, two pain surveys were taken before and after MRI. Before the MRI was taken, participants were evaluated by a physician for potential exclusion criteria (i.e., opioids use). From our sample, 133 responded in both pain surveys to have CP, while 214 denied having CP. When comparing groups, results showed significant differences in health-related questionnaires, but no differences in SyS. Within the pain group, helplessness (β=.325; p=.003), higher DMN (β=.193; p=.037), and lower DAN segregation (β=-.215; p=.014) were strongly associated with a worsening in pain experience over time. Moreover, helplessness moderated the association between DMN segregation and pain experience progression (p=.003). Our findings indicate that the efficient functioning of these networks and catastrophizing could be used as predictors of pain progression, bringing new light to the influence of the interplay between psychological aspects and brain networks. Consequently, approaches focusing on these factors could minimize the impact on daily life activities.